The Effect of Media Songs and Props on Increasing Interest in Eating Nutritious Food for Children - Hartati Ramadhany Pasya; Asep Bayu Dani Nandiyanto (Universitas Komputer Indonesia, 2022)
This study aims to determine how the influence of media songs and props on increasing interest in eating nutritious food for children. The research method used is a descriptive qualitative method with data collection techniques through questionnaires filled out by 12 early childhood children consisting of four boys and eight girls. This research was conducted in 3 stages, namely (1) pre-test, (2) socialization through songs and props; (3) final test. The results showed there was a change in children's interest in eating nutritious foods, as well as a decrease in children's interest in eating foods that were categorized as less nutritious. This means, the media song and props are quite successfully used in early childhood. From each result of data analysis, it can be seen that the media song and props have a positive impact on increasing interest in eating nutritious food at an early age in Cigugurgirang, Parongpong, Indonesia. With this research, it is expected to increase children's interest in consuming nutritious food so their Nutritional Adequacy Rate (RDA) will be fulfilled.